Comparison of Two Methods for Estimation of Glomerular Filtration Rate: Double Plasma Sampling Method and Renography with 99mTc-DTPA - Thi Kim Dung, Nguyen; Thi Phuong, Nguyen; Van Thuyet, Dinh; Dang Tung, Pham; Thang, Nguyen Quoc (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 4, 2021)
: Glomerular filtration rate (GFR) is a crucial metric that is widely used to evaluate kidney function. A method with high accuracy to estimate GFR is renal scintigraphy using radiopharmaceutical 99m-technetium diethylenetriamine pentaacetic acid ( 99m Tc-DTPA) in SPECT (single-photon emission tomography) system. In addition, there is another method, the double plasma sampling method (DPSM) using the same radiopharmaceutical to determine GFR. This study aims to evaluate and compare GFR results collected from 42 patients by the two methods. The result indicates that the two methods have a high correlation with r = 0.857 and r = 0.711 (p<0.05), respectively in the two patient groups. Therefore, DPSM shows a high possibility for clinical application in certain situations. Keywords: 99m Tc-DTPA, glomerular filtration rate, renography. References [1] K. Itoh, Comparison of Methods for Determination of Glomerular Filtration Rate: Tc-99m-DTPA Renography, Predicted Creatinine Clearance Method and Plasma Sample Method, Annals of Nuclear Medicine, Vol. 17, No. 7, 2003, pp. 561-565, https://doi.org/10.1007/BF03006669. [2] J. O. Hernandez, A. R. Torres, F. C. Rodriguez, Comparison of Four Methods for Measuring Glomerular Filtration Rate by Inulin Clearance in Healthy Individuals and Patients with Renal Failure, Nefrologia, Vol. 30, No. 3, 2010, pp. 324-330, https://doi.org/10.3265/Nefrologia.pre2010.Mar.10238. [3] L. A. Stevens, A. S. Levey, Measured GFR as a Confirmatory Test for Estimated GFR, Journal of the American Society of Nephrology, Vol. 20, No. 11, 2009, pp. 2305-2313, https://doi.org/10.1681/asn.2009020171. [4] F. J. Hoek, F. A. Kemperman, R. T. Krediet, A Comparison Between Cystatin C, Plasma Creatinine and the Cockcroft And Gault Formula for the Estimation of Glomerular Filtration Rate, Nephrology Dialysis Transplantation, Vol. 18, No. 10, 2003, pp. 2024-2031, https://doi.org/10.1093/ndt/gfg349. [5] W. S. Watson, A Simple Method of Estimating Glomerular Filtration Rate, European Journal of Nuclear Medicine and Molecular Imaging, Vol. 19, No. 9, 1992, pp. 827, https://doi.org/10.1007/bf00182829. [6] P. W. Blue, J. H. Jackson, N. Ghaed, Re: Glomerular Filtration Rate Determined in Conjunction with Routine Renal Scanning, Radiology, Vol. 156, No. 2, 1985, pp. 553, https://doi.org/10.1148/radiology.156.2.553-a. [7] G. F. Gates, Split Renal Function Testing Using 99m-Tc DTPA. A Rapid Technique for Determining Differential Glomerular Filtration, Clinical Nuclear Medicine, Vol. 8, No. 9, 1985, pp. 400-407, https://doi.org/10.1097/00003072-198309000-00003. [8] K. W. Tobis et al., Difference in Estimated GFR with Two Different Formulas in Elderly Individuals, International Urology and Nephrology, Vol. 38, No. 2, 2006, pp. 381-385, https://doi.org/10.1007/s11255-006-0065-7. [9] C. D. Russell et. Al., Measurement of Glomerular Filtration Rate: Single Injection Plasma Clearance Method Without Urine Collection, Journal of Nuclear Medicine, Vol. 26, No. 11, 1985, pp. 1243-1247. [10] M. J. Surma, A. Plachcinska, J. Kusmierek, Modification of a Two Blood Sample Method Used for Measurement of GFR with 99mTc-DTPA, Nuclear Medicine Review - Central & Eastern Europe, Vol. 21, No. 1, 2018, pp. 43-47, https://doi.org/10.5603/nmr.2018.0013. [11] J. S. Fleming et al., Guidelines for the Measurement of Glomerular Filtration Rate Using Plasma Sampling, Nuclear Medicine Communications, Vol. 25, No. 8, 2004, pp. 759-769, https://doi.org/10.1097/01.mnm.0000136715.71820.4a. [12] A. Piepsz et al., Guidelines for Glomerular Filtration Rate Determination in Children, European Journal of Nuclear Medicine and Molecular Imaging, Vol. 28, No. 3, 2001, pp. BP31-BP36.